A note on the effects of remittances and overseas migration on some Philippine statistics - Daway, Sarah Lynne S.; Ducanes, Geoffrey M. ([Quezon City] School of Economics, University of the Philippines, 2015)
The Philippines is peculiar in that a significant portion of its population is dispersed globally, sending remittances that have exceeded 8 percent of its gross domestic product (gdp) in recent years. For the last two decades, the country has enjoyed a steady flow of remittances from overseas Filipino workers, which has not only provided an additional source of disposable income to domestic households but has also served as a buffer against economic downturns. This note shows that standard gdp accounting and current labor statistics may inadequately account for remittances and overseas migration, especially their corresponding welfare consequences. A better valuation of welfare and living standards requires alternative measures that would better capture the migration phenomenon.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 115-116)
Keywords: Migrant remittances -- Philippines; Migrant labor -- Economic aspects; Emigration and immigration